Double-clad thulium/ytterbium co-doped octagonal-shaped fibre for fibre laser applications - Babar, I.M.; Sabran, M.B.S.; Jusoh, Z.; Ahmad, Harith; Harun, Sulaiman Wadi; Halder, A.; Paul, M.C.; Das, S.; Bhadra, S.K. (Institute of Physical Optics, 2014)
We investigate the lasing performance of a new double-clad thulium/ytterbium co-doped octagonal-shaped fibre, basing on a cladding pump technique. The fibre is fabricated with the aid of a modified chemical vapour deposition combined with a solution doping technique. It is characterized by the Tm3+- and Yb3+-cladding absorptions equal to 0.325 and 3.3 dB/m respectively at 790 and 976 nm. A triple-wavelength fibre laser operating at 1914.5, 1934.7 and 1953.6 nm is built that uses a 5 m long fibre in a ring configuration as a gain medium. With the fibre as long as 15 m, the ring laser produces the highest output power of 21.9 mW at the pump power of 3600 mW, with the lowest threshold pump power being equal to 1000 mW. When operating at 1961.4 nm, the maximal efficiency of 0.88 per cent is achieved for the gain medium length fixed at 10 m. We also demonstrate a Q-switched thulium/ytterbium-doped fibre laser that operates at 1977.5 nm and utilizes multi-walled carbon nanotubes as a gain medium. By varying the multimode 905 nm pump power from 1591.3 to 2261.5 mW, one can increase the pulse repetition rate from 18.8 to 50.6 kHz, while the pulse width then decreases from 8.6 to 1.0 µs. The maximum pulse energy 5.71 nJ is obtained at the pump power 2100 mW.